Evaluating the Implementation of a “COVID-19 Test” Chief Concern in the Emergency Department - Collin Michels; Daniel J. Hekman; Rebecca J. Schwei; Ryan E. Tsuchida; Joshua Gauger; Irene Hurst; Joshua Glazer; Jenna Brink; Ciara Barclay-Buchanan; Manish N. Shah; Azita G. Hamedani; Michael Pulia (Western Journal of Emergency Medicine)
Background: During the COVID-19 pandemic, rapid, at-home testing for severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) was inconsistently available. Consequently, for some patients, emergency departments (ED) became the preferred site to access COVID-19 testing. To improve operational efficiency, our ED implemented a “COVID-19 Test” chief concern (CC). Our primary objective in this analysis was to broadly assess the utilization of the new “COVID-19 Test” CC and associated clinical care. Methods: We conducted a retrospective analysis of ED encounters from an academic ED and an affiliated, community-based ED of all patients after the establishment of a CC of “COVID-19 Test” from October 11, 2021–July 31, 2022. The data were extracted from the electronic health record. We calculated descriptive demographic statistics and ran a univariate and multivariate logistic regression with additional diagnostic or therapeutic interventions (binary) as the outcome variable to generate odds ratios (OR) and 95% confidence intervals (CI). Results: A total of 320 patients were assigned a “COVID-19 Test” CC by a triage nurse. This was 0.5% of all ED encounters in this time frame. Of those, 45% were found to be SARS-CoV-2 positive. Admission or repeat ED visit at 72 hours occurred in 5.3% of patients. Nearly half (46.9%) of patients assigned a “COVID-19 Test” CC underwent additional ED interventions. Patients on Medicaid and those who self-identified as Black or Hispanic/Latino were disproportionately represented in the “COVID-19 Test” CC group as compared to the overall ED population. In multivariate analysis, an Emergency Severity Index of 1, 2 or 3 was associated with significantly higher odds of receiving additional interventions compared to ESI of 4 or 5 (adjusted OR: 46.85; 95% CI 13.28–165.26; P <0.001). Conclusion: Patients assigned a chief concern of “COVID-19 Test” had a high COVID-19 positivity rate, often underwent additional ED interventions, and were at low risk of return ED visits or admission. Minoritized and low-income patients were disproportionately represented in the “COVID-19 Test” CC group, highlighting potential disparities in access to at-home COVID-19 testing and implementation of this CC.